Wellbore stability analysis for arbitrary inclined well in anisotropic formations. Issue 6 (October 2020) - Ma, Tianshou; Huang, Jin; Jia, Lichun; Liu, Yang; Qiu, Yi; Zhang, Yun
Abstract: Wellbore instability is a classic rock mechanics problem encountered during drilling and completing. The traditional model for wellbore stability analysis assumes that formation rocks are homogenous, continuous, and isotropic. However, most of the deep formation rocks are naturally anisotropic. Therefore, this study proposes an anisotropic wellbore stability model for an arbitrary inclined well, considering the anisotropic elastic properties, shear strength, and in-situ stress. This model was compared to the traditional model. The equivalent mud weight of collapse pressure (EMWCP) was predicted for three types of typical in-situ stress states, such as normal faulting (NF), strike-slip faulting (SSF), and reverse faulting (RF). The results show that rock anisotropy significantly influenced EMWCP compared to the traditional model. The anisotropy of in-situ stress and shear strength increase the EMWCP, whereas the anisotropy of rock elastic properties decreases the EMWCP. The optimal well path is in the ranges of the attack angle (the angle between the borehole axis and the normal of weak planes) lower than 45°. In other words, the anisotropy shear strength is harmful to keeping wellbore stability, whereas the anisotropy of rock elastic properties is conducive. Thus, the influence of anisotropic shear strength cannot be ignored for wellbore stability analysis, whereas the influence of anisotropic elasticity can be ignored. This model provides theoretical guidance for drilling mud density optimization, well trajectory optimization, and well drilling and completion safety.